The natural resource curse in post-soviet countries: The role of institutions and trade policies - Roman Horváth; Ayaz Zeynalov (Institut für Ost- und Südosteuropaforschung (IOS), 2014)
We examine the effect of natural resource abundance on economic performance during the 1996-2011 period in the 15 independent countries that formerly comprised the Soviet Union. These countries were a largely homogeneous group with respect to institutional development, liberalization and economic performance; however, these countries began to demonstrate marked differences from one another with respect to these factors during the transition, which has resulted in unique cross-section and time variation. Using several panel regression models that address the endogeneity issues, our results suggest that natural resources crowd out manufacturing sector unless the quality of domestic institutions is sufficiently high. Conversely, trade policies do not help convert the natural resource curse into a blessing.
urn:nbn:de:101:1-2014070810451
Keywords: O11; O13; Q30; 330; natural resource curse; institutions; manufacturing; post-Soviet countries